Climate-related bilateral official development assistance (ODA) and vulnerability: a comparative study of allocation and effectiveness - Rauniyar, S. K.; Shiiba, N.; Yamasaki, L.; Tomoi, Hiroaki; Tomoi, Hana; West, M. K.; Watanabe, A.; Nomura, S. (2025)
Official Development Assistance (ODA) has emerged as a crucial tool for supporting nations worldwide in mitigating and adapting to the impacts of climate change. This study investigates bilateral ODA allocated to climate change mitigation and adaptation from 2002 to 2021. Data from OECD iLibrary and World Risk Reports were analyzed to explore temporal patterns and sectoral distribution of climate-related ODA. Polynomial regression calculated the estimated average annual percentage change (EAAPC) in adaptation-focused ODA and vulnerability. We also evaluated the relationship between adaptation-focused ODA, vulnerability, and GDP per capita between 2011 and 2021. In 2021, Japan, Germany, and France provided 75% of total bilateral ODA dedicated to climate change. From 2002 to 2021, major donors directed substantial portions of climate-related ODA towards infrastructure, energy, water & sanitation, agriculture, and environmental protection. From 2011 to 2021, the highest EAAPC in vulnerability was observed in the Central African Republic (0.62; 95% CI: 0.60 to 0.64), followed by Papua New Guinea (0.57; 0.55 to 0.59), Yemen (0.50; 0.49 to 0.52), and Guinea-Bissau (0.33; 0.32 to 0.34). Despite their high vulnerability, some of these countries received disproportionately less adaptation-focused ODA. The correlation between vulnerability and adaptation-focused ODA revealed a complex regional relationship. Variations in adaptation-focused ODA and vulnerabilities underscore the dynamic relationship between international aid and a nation’s intrinsic capacity to address challenges. This investigation highlights the importance of understanding these dynamics and calls for a re-evaluation of aid allocation. Strengthening climate change initiatives within the ODA framework and tailoring aid distribution to the specific needs of recipient nations in mitigation and adaptation can enhance its effectiveness, resulting in sustainable and impactful outcomes.